Highly efficient flame retardant and smoke suppression mechanism of polypropylene nanocomposites based on clay and allylamine polyphosphate - Xiao, Dan; Zheng, Meng-Ting; Gohs, Uwe; Wagenknecht, Udo; Voit, Brigitte; Wang, De-Yi (Journal of Applied Polymer Science, 2022)
Fire-retarded polymer nanocomposites (FRPN) based on polypropylene with clay and allylamine polyphosphate (PP/clay-AAPP) were designed and prepared by melt mixing. Their morphological, thermal and fire-safety properties were investigated by TEM, SEM, EDS, TG, UL-94, LOI, cone-calorimeter test and TG-FTIR. The results exhibited that the LOI of PP/2 wt%clay-20wt%AAPP nanocomposites was 29.5% with V-0 rating level in UL-94 vertical testing. Significant enhancements in fire safety performance were also observed for fire-retarded PP nanocomposites from cone-calorimeter test decreasing heat release as well as smoke and toxic gases. PP/clay-AAPP nanocomposites not only provided relatively stable char layer during polymer burning, but also exhibited better fire safety performance due to the exfoliation of clay platelets. It displayed that incorporation of clay and AAPP were very efficient in increasing the fire safety of PP composites.
CRIS-Team Scopus Importer:2022-04-14
Keywords: applications; clay; composites; degradation; flame retardance